A Systematic Investigation on Complement Pathway Activation in Diabetic Retinopathy - Shahulhameed, Shahna; Vishwakarma, Sushma; Chhablani, Jay; Tyagi, Mudit; Pappuru, Rajeev R.; Jakati, Saumya; Chakrabarti, Subhabrata; Kaur, Inderjeet (Frontiers in Immunology, 2020)
The complement system plays a crucial role in retinal homeostasis. While the proteomic analysis of ocular tissues in diabetic retinopathy (DR) has shown the deposition of complement proteins, their exact role in the pathogenesis of DR is yet unclear. We performed a detailed investigation of the role of the complement system by evaluating the levels of major complement proteins including C3, C1q, C4b, Complement Factor B (CFB), and Complement Factor H (CFH) and their activated fragments from both the classical and alternative pathways in vitreous humor and serum samples from proliferative DR (PDR) patients and controls. Further, the expressions of complements and several other key pro- and anti-angiogenic genes in the serum and vitreous humor were analyzed in the blood samples of PDR and non-PDR (NPDR) patients along with controls without diabetes. We also assessed the pro-inflammatory cytokines and matrix metalloproteinases in the vitreous humor samples. There was a significant increase in C3 and its activated fragment C3bα' (110 kDa) along with a corresponding upregulation of CFH in the vitreous of PDR patients, which confirmed the increased activation of the alternative complement pathway in PDR. Likewise, a significant upregulation of angiogenic genes and downregulation of anti-angiogenic genes was seen in PDR and NPDR cases. Increased MMP9 activity and upregulation of inflammatory markers IL8 and sPECAM with a downregulation of anti-inflammatory marker IL-10 in PDR vitreous indicated the possible involvement of microglia in DR pathogenesis. Further, a significantly high C3 deposition in the capillary wall along with thickening of basement membranes and co-localization of CFH expression with CD11b+ve activated microglial cells in diabetic retina suggested microglia as a source of CFH in diabetic retina. The increased CFH levels could be a feedback mechanism for arresting excessive complement activation in DR eyes. A gradual increase of CFH and CD11b expression in retina with early to late changes in epiretinal membranes of DR patients indicated a major role for the alternative complement pathway in disease progression.